The relationship between the safety of prescribed chemotherapy and adherence to breast cancer guidelines in a level three hospital. Issue 2 (12th March 2012) - Alañón, A.; Ubago, R.; Ferrit, M.; Cancela, B.; Araque, P.; Calleja, M.A.
Abstract : Background: Some studies suggest that compliance with clinical practice guidelines (CPGs) for breast cancer is related to improved patient safety. Purpose: To analyse the compliance of chemotherapy prescriptions in a third level hospital with the breast cancer Integrated Care Process (ICP) and the protocol established by the Spanish Society of Gynaecology and Obstetrics (SEGO), and to analyse the relationship between safety and compliance with each protocol. Materials and methods: Retrospective observational study of patients diagnosed with breast cancer in 2006 and subsequently treated with chemotherapy; patients were followed up until December 2010. 'Compliance' was defined by the fulfilment of all recommended criteria: indication, regimen, dose, number and frequency of cycles. Toxicity was assessed as the number of admissions for this reason and as the number of chemotherapy-induced adverse reactions (ARs). Both the regional ICP and the national SEGO protocol were published in 2005. Results: The study included 131 patients, who received a total of 189 treatments. Compliance with the ICP was observed in 27% of cases and with the SEGO protocol in 21.7%. ARs were recorded in 61 patients and admittances for toxicity in 34. The mean no. of admissions for toxicity per patient was 1 for those receiving ICP-compliant treatment and 0.94 for those who were not (p=0.748); the mean no. of ARs was 4.6 in those receiving ICP-compliant treatment and 3.1 in those who were not (p=0.232). The mean no. of admissions was 3 for those receiving SEGO-compliant treatment and 0.81 for those who were not (p=0.010); the mean no. of ARs was 7.5 in those receiving SEGO-compliant treatment and 2.9 in those who were not (p=0.003). Conclusions: Compliance of prescriptions with ICP and SEGO guidelines is low and does not appear to be directly related to a reduction in chemotherapy-induced toxicity in breast cancer.